2013
DOI: 10.1128/jvi.01145-13
|View full text |Cite
|
Sign up to set email alerts
|

Topological Analysis of HIV-1 Glycoproteins Expressed In Situ on Virus Surfaces Reveals Tighter Packing but Greater Conformational Flexibility than for Soluble gp120

Abstract: bIn natural infection, antibodies interact with HIV-1 primarily through nonfunctional forms of envelope glycoproteins (Env), including uncleaved (UNC) gp160 and gp41 stumps. These antigens are important to fully characterize, as they may be decoys that promote nonneutralizing responses and may also be targets for nonneutralizing effector responses. In this study, we compared the antigenic properties of Env expressed in situ on pseudovirion virus-like particle (VLP) surfaces and soluble gp120 using harmonized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 95 publications
1
27
0
Order By: Relevance
“…For example, multiple non-NAbs are much more reactive with various gp120 epitopes on uncleaved trimers, as are ones to the six-helix bundle form of gp41 (13,(26)(27)(28). Thus, we believe that the aberrant soluble gp140 structures that we have visualized by EM will have their counterparts on the surface of cells expressing uncleaved Env proteins.…”
Section: Sosr6mentioning
confidence: 91%
See 2 more Smart Citations
“…For example, multiple non-NAbs are much more reactive with various gp120 epitopes on uncleaved trimers, as are ones to the six-helix bundle form of gp41 (13,(26)(27)(28). Thus, we believe that the aberrant soluble gp140 structures that we have visualized by EM will have their counterparts on the surface of cells expressing uncleaved Env proteins.…”
Section: Sosr6mentioning
confidence: 91%
“…Cleaved and uncleaved, soluble or membrane-bound trimers express NAb and non-NAb epitopes very differently (13,(26)(27)(28). We therefore assessed the antigenicity of purified, D7324-tagged versions of SOSIP.R6, SOSIP.SEKS, and WT.SEKS gp140 trimers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, sCD4 (57) and MAbs directed against gp41 (58) do cause gp120/gp41 dissociation. These cooperative interactions probably result from the structural flexibility of this Env in its native state and the conformational alterations that have been observed to result upon CD4 or MAb binding (59)(60)(61).…”
Section: Resultsmentioning
confidence: 99%
“…Past studies also have reported the activation of Lck and the downstream signals upon CD4 engagement by the HIV virions or the HIV Env expressed on cells (51)(52)(53). On the surfaces of virions and infected cells, heterogeneous species of the HIV Env glycoproteins are expressed (54)(55)(56), including nonfunctional Env proteins that cannot partake in the virus entry process but may have immunomodulatory activities demonstrated in this study.…”
Section: Discussionmentioning
confidence: 85%